High parasite prevalence driven by the human-animal-environment interface: a One Health study in an urban area in southern of Chile - Sanhueza Teneo, Daniel; Cerna, Omar; Chesnais, Cédric B.; Cárdenas, David; Camus, Paula (Frontiers in Veterinary Science, 2025)
Parasitic infections remain a global health concern, affecting human populations worldwide. However, comprehensive studies evaluating human, animal, and environmental interactions driven transmission of parasites are limited. We conducted a One Health study in an urban area of Valdivia, Chile. Human participants provided fecal and blood samples for parasitological and serological analysis. Environmental soil samples were collected from public parks, and fecal samples from owned and stray dogs were analyzed. Detection of intestinal parasites employed microscopy and molecular techniques, including next-generation sequencing (NGS), while anti-Toxocara canis antibodies in humans were assessed using ELISA. Socioeconomic surveys explored risk factors associated with parasitism. Parasite prevalence was 28% in humans, 26% in owned dogs, and 44% in environmental dog feces. Anti-T. canis IgG antibodies were present in 33% of humans. Soil contamination was identified in up to 30.5% of park samples, harboring zoonotic parasites such as Toxocara sp. and Trichuris vulpis, the same species identified in environmental dog feces. Zoonotic subtypes of Giardia duodenalis and Blastocystis sp. were detected in humans. Our findings highlight significant zoonotic and environmental transmission contributing to human parasitic infections in urban settings, underscoring the need for integrated public health interventions. This study demonstrates the importance of adopting an OneHealth approach in the study of parasitology. The complex ecology of parasites requires an integrated perspective to fully understand their transmission pathways and develop effective control strategies. By emphasizing the interconnectedness of human, animal, and environmental health, we aim to contribute to the management and mitigation of this persistent public health issue.